Pembuatan Dan Karaktrisasi Karbon Aktif Berbahan Dasar Cangkang Sawit Dengan Metode Aktivasi Fisika Menggunakan Rotary Autoclave - Ibrahim Ibrahim; Awaludin Martin; Nasruddin Nasruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Activated carbon  is an  absorbent  that  has  widely used  because it’s  high absorption  capacity. Necessity  to improve  the quality of activated carbon made from palm shells with low price and easy to obtain. The process of preparation and characteristics of activated carbon conducted in this research  using  physical activation  using  CO2  as the  activating agent.  Carbonization  and activation processes performed in a rotating  furnace  (rotary  autoclave) by flowing nitrogen gas (N2) at 100 ml/min and CO2 flow rate of 250 ml/min. Carbonization temperature 500oC was used with some variation of carbonization time, activation time and activation temperature. The results seen with activated carbon characteristics knowing  iodine numbers obtained  from any activated carbon  produced. Optimum  characteristics of  activated carbon  obtained  by  activation  at  750oC temperature,  the duration of carbonization and activation of activated carbon produced during 2 hours with 603 g / kg of iodine number.Keywords: Rotary Autoclave, iodine, Activated Carbon.